Prevalence of Non Alcoholic Fatty Liver Disease (NAFLD) among Adults Aged 30 Years and Above in a Rural Population of Jammu- An Observational Study - Anuj Kapoor; Shoket Chowdary; Deepika Dewan; Ghanshyam Dev; Rashmi Kumari; Dinesh Kumar (Medsci Publications, 2018)
Background: Non alcoholic fatty liver disease (NAFLD) is one of the most common causes of chronic liver disease globally and its burden is increasing in India. There is still paucity of knowledge regarding the actual burden and risk factors of NAFLD especially in rural areas. Methodology: The present study was conducted in six villages under Health and Demographic Surveillance System (HDSS) in Block RS Pura. A total of 322 adults aged 30 years and above were selected using simple random sampling to estimate the prevalence of NAFLD . The number of eligible participants as per inclusion criteria were 258 and Out of them, finally 250 participants reported for undergoing ultrasonography of the liver,  anthropometry, blood pressure recording, and biochemical tests . Results: Prevalence of NAFLD was 37.2% (31.4-43.3). Majority of participants had mild severity (57%). Persons with low physical activity and high BMI (both overweight and obese persons) had maximum prevalence of NAFLD 66.7%, 26.2% and 43.07% respec- tively. Hypertensives and women with higher waist hip ratio also reported higher prevalence. Regarding biochemical levels, the prevalence was higher in subjects having high SGOT (69.8%), SGPT (43.5%), serum alkaline phosphates (43.4%) and serum LDL levels(64.4%). Conclusions: The prevalence of NAFLD is high in rural areas of India.